2014
DOI: 10.1515/med-2015-0019
|View full text |Cite
|
Sign up to set email alerts
|

Relation between bone mineral density and IL-17 serum levels in Serbian patients with early Rheumatoid arthritis

Abstract: AbstractRheumatoid arthritis (RA) is a chronic inflammatory disease characterized by synovial inflammation and destruction of joint cartilage and bone. Different cytokines play important role in the processes that cause articular destruction and extra-articular manifestations in RA. The contribution of cytokines representing the Th1 (INF-γ), Th2 (IL-4) and IL-17A to the pathogenesis of early RA and bone mineral density (BMD) loss in still poorly understood. Serum samples of 38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…All patients involved in the trials met the criteria of the American College of Rheumatology from 2010 as well as other criteria described in the previous study. [1011121314] The patients were divided into two groups: Group I patients - no visible changes in the macula (26 patients) and Group II patients - with visible changes in the macula (30 patients). Patients with glaucoma, ocular hypertension, optic nerve diseases, diabetes, diseases of the retina and the macula, uveitis, chorioretinitis, defects in the visual field, including the central 10 degrees, prior ophthalmic surgery, and larger refractive errors (greater than ± 6D spheres and/or greater than ± 3D cylinder) were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…All patients involved in the trials met the criteria of the American College of Rheumatology from 2010 as well as other criteria described in the previous study. [1011121314] The patients were divided into two groups: Group I patients - no visible changes in the macula (26 patients) and Group II patients - with visible changes in the macula (30 patients). Patients with glaucoma, ocular hypertension, optic nerve diseases, diabetes, diseases of the retina and the macula, uveitis, chorioretinitis, defects in the visual field, including the central 10 degrees, prior ophthalmic surgery, and larger refractive errors (greater than ± 6D spheres and/or greater than ± 3D cylinder) were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Both agreeing and conflicting results can be found in the literature. For example, one study reported that IL-17, but not IL-4, was moderately correlated with DAS28ESR and ESR [ 49 ], while another reported that IL-17 did not correlate with either DAS28 [ 50 ] or ESR [ 50 , 51 ]. These discrepancies may have resulted from differences between study populations (e.g., regarding age, disease severity, disease stage, proportion of males and females, genetic background, comorbidities, or medications), technical differences (e.g., regarding medical practices or data collection and analysis), or a combination of both.…”
Section: Discussionmentioning
confidence: 99%
“… 165 , 166 Ankylosing spondylitis (AS), like PsA, causes higher levels of IL-17A in patients’ serum and synovial fluid. 164 , 167 Emerging evidence suggests that IL-17F plays a significant role in spondyloarthritis spectrum illness and psoriasis, and dual inhibition of IL-17A and IL-17 may be beneficial, particularly in the skin. 168 IL-17F production in response to inflammatory stimuli can activate the C/EBP protein, which mediates osteoblastogenesis during early fracture repair.…”
Section: Il-17-driven Physiological Responsesmentioning
confidence: 99%